Cardiovascular Proteomics
DOI: 10.1385/1-59745-214-9:181
|View full text |Cite
|
Sign up to set email alerts
|

The Proteome of Endothelial Cells

Abstract: Endothelial cells form a continuous monolayer lining the inside face of all blood vessels, and present the ability to selectively control vascular permeability. The endothelium is involved in a wide variety of normal physiological and pathological processes. The endothelial dysfunction occurs under activation conditions, with the acquisition of many new functional, inflammatory, and immune properties, and as a consequence, endothelial cells display many different transcription profiles. We describe here the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Antioxidant molecules in the endothelium have been reported in previous proteomic studies, although only a very small number were ever identified [63, 64]. High antioxidant activity has also been suggested for endothelial progenitor cells [65], and large contents of peroxide detoxifying enzymes were demonstrated at the blood-brain barrier long ago [66].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant molecules in the endothelium have been reported in previous proteomic studies, although only a very small number were ever identified [63, 64]. High antioxidant activity has also been suggested for endothelial progenitor cells [65], and large contents of peroxide detoxifying enzymes were demonstrated at the blood-brain barrier long ago [66].…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells are currently the most commonly used in vitro model. A differential proteomic approach using these cells under basal quiescent conditions and activated by stimulation with proinflammatory cytokines, such as interleukin-1 , has been recently published [15]. The analysis of a series of 2DE gels allowed the selection of 233 proteins and showed that 70% of them had an increase and 30% a decrease in the expression levels in activated cells.…”
Section: Cell and Tissuementioning
confidence: 99%
“…In 2006, González-Cabrero et al published a chapter detailing methods of EC proteome characterization. They provided a 2-DE map of the endothelial proteome detecting 600 protein spots using 4.0–7.0 pH range IPG strips [38] .…”
Section: Proteomic Characterization Of Endotheliummentioning
confidence: 99%